Pseudotumoral form of cerebral Schistosomiasis Mansoni - Romero, F. R. [UNESP]; Zanini, M. A. [UNESP]; Ducati, L. G. [UNESP]; Gabarra, R. C. [UNESP]; Haddad, G.R. [UNESP]; Souza, V. de [UNESP] (Journal of Surgical Case Reports, 2012)
The authors report a case of 36-year-old woman presented with epileptic seizures and headaches. Magnetic resonance imaging (MRI) revealed an enhancing lesion with surrounding edema and mild mass effect in the left frontal lobe. Stereotactic brain biopsy demonstrated intraparenchymal granulomas surrounding S. mansoni eggs. Praziquantel was started (60mg/kg of body weight, in a single dose), followed by Prednisone (80mg/day) for seven days to treat the cerebral edema. The patient's symptoms resolved following medical treatment and the follow-up MRI yielded normal findings.